P-017 M2 Occlusions as a Target for Endovascular Therapy: Comprehensive Analysis of Diffusion/Perfusion MRI, Angiography, and Clinical Outcomes. (26th July 2014) - Sheth, S; Saver, J; Jahan, R; Starkman, S; Duckwiler, G; Tateshima, S; Gonzalez, N; Liebeskind, D; Stroke Investigators, Ucla
Abstract : Introduction: The ideal population of patients for endovascular reperfusion therapy (ERT) in acute ischemic stroke (AIS) remains undefined. Recent trials have moved towards including only patients with proximal (ICA or M1) occlusions. We characterise the imaging and clinical characteristics of distal (M2) compared to proximal (M1) MCA occlusions in patients undergoing ERT, and determine the effect of successful ERT in patients with M2 occlusions. Materials and methods: From a prospective registry, all patients treated in clinical practice with ERT for AIS with M1 MCA or M2 MCA occlusions from 9/2004 to 12/2012 were identified. Detailed MRI imaging as well as angiographic data were reviewed and scored in a blinded manner. Patients were excluded if tandem lesions (i.e. ICA + M1 or M2) were identified. Results: We identified 61 patients with M1 and 52 with M2 occlusions. There were no differences between M1 and M2 patients with respect to age (66 vs. 69, p = 0.42) and female gender (67% vs. 50%, p = 0.12). There was a trend towards lower NIHSS in the M2 group (16 vs. 11, p = 0.07). Compared to M1 occlusions, patients with M2 occlusion presented with lower infarct volumes (15 vs. 11 mLs, p < 0.05) and hypoperfused volumes (84 vs. 46 mLs, p < 0.05). There was a trend towards prolonged door to groin puncture for M2 cases (121 vs. 150 min, p = 0.5). Rates of any haemorrhage type were higher in the M1 vs. M2 population (56% vs. 21%, p < 0.05). There was no difference in TICI 2b/3 recanalization rates (46% vs. 37%, p = 0.31). Final infarct volumes were lower in patients with M2 occlusions (52 vs. 22 mL, p < 0.05), for both patients who achieved TICI 2b/3 (42 vs. 8 mL, p < 0.05), and those who did not (75 vs. 51 mL, p < 0.05). 94% of M2 patients who received IV tPA were found to have persistent occlusions on angiography. Patients with M2 occlusions who achieved TICI 2b/3 recanalization had lower infarct volumes (8 vs. 51 mL, p < 0.05) and decreased infarct expansion (1 vs. 19 mL, p < 0.05) compared to those that did not. M2 patients who received IV tPA but did not progress to TICI 2b/3 recanalization developed larger final infarct volumes (64 vs. 8 mL, p < 0.05) and greater infarct expansion (17 vs 1 mL, p < 0.05). TICI 2b/3 reperfusion was associated with improved mRS at discharge (p < 0.05, Van Elteren shift analysis). M2 patients who received IV tPA but did not progress to TICI 2b/3 had worse discharge mRS outcomes (p < 0.05). Conclusion: In patients undergoing ERT compared to those with M1 occlusions, patients with M2 occlusions presented with smaller infarcts and developed less haemorrhage. In patients with M2 occlusions, successful reperfusion with ERT was associated with smaller final infarcts, decreased infarct expansion, and improved clinical outcomes. IV tPA was not sufficient in recanalizing many M2 occlusions. Patients with M2 occlusions benefit from ERT when tPA cannot be given or has failed to recanalise the vessel. Disclosures: S. Sheth: None. J. Saver: None. R. Jahan: None. S. Starkman: None. G. Duckwiler: None. S. Tateshima: None. N. Gonzalez: None. D. Liebeskind: None. UCLA Stroke Investigators: None.